Gender equality policy of the Olympic Movement in Chinese sport governing bodies: the case of elite volleyball - Huang Xingmeng Ava; Lau Patrick Wing Chung (Translational Exercise Biomedicine, 2024)
This research based on the theoretical framework of globalisation focuses on the development of gender equality policy in the Olympic Movement and the implementation of IOC’s gender equality policy in the context of Chinese elite volleyball.